PENGAWASAN DAN KEPUASAN KERJA KARYAWAN TERHADAP PELAYANAN PADA BENGKEL MOTOR HONDA MERANTI - SOVIA LOLITA APRIANI PARDEDE; HAPCIN SUHAIRY; CORINNA WONGSOSUDONO (LP2MTBM MAKARIOZ, 2019)
This Research is an empirical research about “The Influence of Control and Employee Job Satisfaction on Society Service in Honda Meranti Motorcycle Repair Shop”. The quantitative and qualitative data are analyzed by using SPSS version 15. Validition test is done by comparing between r table value with r counted value (correlated-itemtotal correlation). If r counted value > r table, so the item is valid. Reliability is measured by Cronbach alpha > 0,5 shows that testing requirement is fulfilled. It hypothesis is tested by using or seeing the coefficient table result at t value ( t sig. or t significant) H1 = 0,000 or probability is below 0,05 and H2 = 0,004 or probability is below 0,05, it shows that H1 and H2 are accepted means that there is an influence of tight control and job satisfaction on society service in Honda Meranti Motorcycle Repair Shop. Hypothesis testing (H3) uses ANOVA table on F value (F sig or F significance) = 0,000 or probability far below 0,05. It shows that H3 is accepted means that there is the influence of tight control on job satisfaction simultaneously on society service in Honda Meranti Motorcycle Repair Shop. Regression on the influence of control and job satisfaction on society service in Honda Meranti Motorcycle Repair Shop shows that determinant coefficient (R2) = 0,592 (59,2%) and statistically significant (P ≤ 0,05). This result shows only 59,2% in tight control variable and job satisfaction are explained simultaneously influence on society service, the rest is 40,8% is explained by other independent variable that cannot be observed in this research.